Unified divergent strategy towards the total synthesis of the three sub-classes of hasubanan alkaloids - Li, Guang (Nat Commun, 2021)
Elegant asymmetric synthesis of hasubanan alkaloids have been developed over the past decades. However, a divergent approach leading to all three sub-classes of this family of natural products remains unknown. We report herein the realization of such an endeavor by accomplishing enantioselective total syntheses of four representative members. The synthesis is characterized by catalytic enantioselective construction of the tricyclic compounds from which three different intramolecular C-N bond forming processes leading to three topologically different hasubanan alkaloids are developed. An aza-Michael addition is used for the construction of the aza-[4.4.3]-propellane structure of (-)-cepharamine, whereas an oxidation/double deprotection/intramolecular hemiaminal forming sequence is developed to forge the bridged 6/6/6/6 tetracycle of (-)-cepharatines A and C and a domino bromination/double deprotection/cyclization sequence allows the build-up of the 6/6/5/5 fused tetracyclic structure of (−)-sinoracutine.